Basic principles in creating programs for the education of nurses and midwives - Saveljić Mitar M.; Pelčić Damir N.; Boljević Tanja V. (Srpsko lekarsko drustvo, 2023)
Introduction: The this paper the authors describe the development of the education program for nurses in public health in the European Union (EU). Methods: This paper will present information from relevant professional/scientific data sources about the basic principles in the development of nursing and midwifery education programs, which will contribute to the development of new competencies of nurses in the field of health care and public health. The paper provides an overview of the Munich Declaration, followed by an overview of the educational systems for nurses and midwives in several countries of Western Europe and the Balkans. Topic: The authenticity of health care evaluation ensures the conditions for strengthening nurses' awareness of the value of their own profession and the independence of acquired competencies and skills from inappropriate external interference. Recognizing the profession or authenticity of nursing requires more education. All questions and reflections are focused on the identity and authenticity of the profession, emphasizing the value of nursing care, as well as the aspiration that the development of the nursing profession remains within the framework of the fundamental value. Conclusion: Today, nurses make a significant contribution to the health care system of a country at all levels of health care. In order to achieve the professionalization of nursing, it is necessary to transform nurses, which implies a high level of quality knowledge and skills, as well as an awareness of moral and ethical responsibility towards patients, colleagues and oneself.